Analysis of Land Use Alignment with Spatial Pattern Plan In Batang District, Central Java - Ali Masrochan; Ernan Rustiadi; Darmawan Darmawan (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the alignment of land use with the spatial planning pattern of the Regional Spatial Planning (RTRW) in Batang Regency, Central Java Province. The research utilizes the land use map of Batang Regency from 2021 and the Batang Regency spatial planning map for 2019-2039. The largest land use in Batang Regency is paddy fields, covering an area of 17,483.57 hectares or 20.39% of the total land area. The alignment analysis results reveal that 47,465.63 hectares or 55.36% of land use in Batang is consistent with the spatial planning pattern, 33,814.25 hectares or 39.44% is potentially consistent, and 4,462.25 hectares or 5.20% is not consistent with the spatial planning pattern or its designated purpose. The findings highlight the need for targeted policy interventions to enhance land use conformity with the spatial planning framework to promote sustainable development in Batang Regency.